New Exact Solutions of the mBBM Equation (Journal of Atomic and Molecular Sciences, 2014)
The enhanced modified simple equation method presented in this article isapplied to construct the exact solutions of modified Benjamin-Bona-Mahoney equation.Some new exact solutions are derived by using this method. When some parametersare taken as special values, the solitary wave solutions can be got from the exactsolutions. It is shown that the method introduced in this paper has general significancein searching for exact solutions to the nonlinear evolution equations.
Keywords: modified Benjamin-Bona-Mahoney equation; exact solutions; enhanced modified simple equation method.